Norms under Challenge: Unpacking the Dynamics of Norm Robustness. Issue 1 (20th February 2019) - Deitelhoff, Nicole; Zimmermann, Lisbeth
Abstract: The introduction develops this special issue's main research question: under which conditions are challenges to norms likely to decrease their robustness? The issue presents current research on contestation and norm robustness and discusses its limitations. We conceptualize a norm's robustness by examining both the practical and discursive dimensions. Robustness is high when norm addressees express widespread discursive acceptance of a norm's claims (validity) that also generally guide addressees' actions (facticity). When normative claims are discursively rejected by most addressees and do not guide their actions, robustness is low. The contributions develop four broad indicators for measuring robustness (concordance, third-party reactions to norm violation, compliance, and implementation). The norms analyzed here were not easily eroded; despite direct challenges, they remained surprisingly robust. This indicates that norm robustness is not determined by the relative power of norm challengers, but rather types of contestation and structural factors. These include being embedded in larger normative structures, institutionalization, and legal character, although effects of these factors are more ambivalent than norm research has usually supposed.